Modal Sosial Kelompok Sadar Wisata (Pokdarwis) Dalam Mengembangkan Wisata Embung Terpadu di Kampung Dayun Kabupaten Siak - Putri, Ningsi; Resdati, Resdati; Armilus, Robi; Widodo, Teguh (Jurnal Ilmiah Wahana Pendidikan, 2026)
The Tourism Awareness Group (Pokdarwis) of Kampung Dayun serves as a platform for community members to actively participate in the development of local tourism, particularly the Embung Terpadu tourism site. The group’s success in achieving its goals is closely tied to its social capital. This study was conducted in Kampung Dayun, Dayun District, Siak Regency, and aims to explore the social interactions among Pokdarwis members and identify the elements of social capital involved in the development of the Embung Terpadu tourism site. A qualitative descriptive method was employed, using purposive sampling to select participants. The study involved seven informants: five Pokdarwis members, one community member collaborating with Pokdarwis, and one key informant the head of Kampung Dayun. Data were collected through observation, in depth interviews, and documentation, utilizing both primary and secondary sources. This research applies Robert D. Putnam’s theory of social capital. The findings reveal three key elements of social capital: social networks, trust, and social norms. These elements have facilitated strong collaboration among Pokdarwis members, between Pokdarwis and the local community, and between Pokdarwis and its partners. Through social networks, the group has accessed both physical and non physical support for tourism development. Trust has strengthened partnerships, while social norms have provided structure and guidance for collaborative efforts